A Cross‐Cultural Examination of Auditors' Willingness to Relocate in Public Accounting: Evidence from Hong Kong and the United States. Issue 1 (22nd September 2015) - Law, Philip; Yuen, Desmond; Lei, Adrian
Abstract : This empirical study examines the determinants of factors influencing auditors' willingness to relocate nationally and internationally in public accounting on two cultural dimensions. This is the first study in the cross‐cultural literature to examine this under‐researched issue. A theoretical model is developed from family systems theory and social role theory. Logistic regression models (Models 1–16) are performed. While a cultural difference between auditors in the United States (US) and in Hong Kong (HK) might have been expected, we find similar results for both groups of auditors. Spouse willingness has the highest explanatory power among the family factor variables. Other family variables are also found to be significant. Male auditors are more willing to relocate nationally and internationally than female auditors. Furthermore, auditors' career plateau has the highest explanatory power among the organizational variables, followed by perceived organizational support and auditors' compensation. Our results support family systems theory and social role theory. A series of sensitivity analyses validate our main results and indicate the robustness of the findings. This study provides important implications for human asset accounting and the cross‐cultural accounting literature.